Cellular and tissue expression of DAPIT, a phylogenetically conserved peptide - Kontro, H. (PAGEPress Publications, 2012)
DAPIT (Diabetes Associated Protein in Insulin-sensitive Tissues) is a small, phylogenetically conserved, 58 amino acid peptide that was previously shown to be down-regulated at mRNA level in insulin-sensitive tissues of type 1 diabetes rats. In this study we characterize a custom made antibody against DAPIT and confirm the mitochondrial presence of DAPIT on cellular level. We also show that DAPIT is localized in lysosomes of HUVEC and HEK 293T cells. In addition, we describe the histological expression of DAPIT in several tissues of rat and man and show that it is highly expressed especially in cells with high aerobic metabolism and epithelial cells related to active transport of nutrients and ions. We propose that DAPIT, in addition to indicated subunit of mitochondrial F-ATPase, is also a subunit of lysosomal V-ATPase suggesting that it is a common component in different proton pumps.